Eminem’s complex techniques of rap flow and poetic rhyme and how they interact with their musical accompaniment: a case study of lose yourself by Eminem / Abang Mohd Mustaqim Abang Ahmat - Abang Ahmat, Abang Mohd Mustaqim (2014)
In general, this study has been conducted to discuss the important parts of Eminem’s complex techniques of rap flow and poetic rhyme and how they interact with their musical accompaniment. A case study of Lose Yourself by Eminem. Therefore, this research study is limited to the song Lose Yourself and various sources pertaining to it. Collectively, the study has unfolded all the aspects of Eminem’s complex techniques of rap flow and poetic rhyme and how they interact with their musical accompaniment. A case study of Lose Yourself by Eminem which are the styles of his rap flow, his writing technique for his rap lyrics using the multisyllable rhymes and the interlocking of his rap as part of the interaction with their musical accompaniment.